Peningkatan Kapasitas Teknik Penulisan Jurnal Ilmiah pada Guru Sekolah - Faizatul Amalia; Tri Astoto Kurniawan; Bayu Rahayudi; Adam Hendra Brata (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Teachers as professional educators should have some competencies, such as pedagogical competence, personal competence, social competence, and professional competence. The focus of this workshop is on the professional competence which its definition is the teacher's ability in mastering broad and in-depth subject matter that allows guiding students to meet the competency standards set in the National Education Standards. There are many activities that can support or enhance the professional competence of teachers, such as writing. By writing, teachers have the opportunity to develop themselves in order to become more creative, active, innovative and professional teachers. The module of X applications usage for vocational teachers can be used to support teacher activities in writing scientific papers. This module will be useful to facilitate the writing of citations in a scientific work. Using the Mendeley application in this workshop, make the teacher to be more insightful which support their research activity, also can improve their motivation to know how the important thing of research in their field. Therefore, this service activity want to give the teacher a knowledge of tips and tricks to facilitate journal writing. There are tools that can be used to make citations in the bibliography, such as the reference feature, Endnote, or Mendeley. So that the teacher's writing will be known and it is easier for teacher to convey the results of his research in relevant journals, especially vocational teachers in Malang.